THE INITIAL ADSORPTION OF Pb2+ TO Dunaliella salina - Moh. Muhaemin (JOURNAL OF COASTAL DEVELOPMENT, 2006)
The adsorption process of metal ion to algal sudace groups and complexes to become organic material at all growth phases could be ajecting their behaviour in seawater. The dwerential pulse anodic stripping voltammetry (DPASIO method was used to determine the adsorption and interaction between the Dunaliella salina and Pbz`. The rate of adsorption was found in two steps; first a relative fast adsorption step (I0 min) and second slower or aw'usion—controlled uptake into the cells. The parabolic equation could be performed ([Pb2+]mr,a = L3 I x I0'7 + 0.062 x 107 V0 to describe the relationship between metal ion adsorption and uptake by the algae as a function of time. The high ajfinity constant is similar to the complexing capacity by the alga and no signylcant effect of cell density on binding capacity. This shows that ligands produced by the algae play an important part in buffering concentration of free metal concentration